Experimental and numerical investigations of diamond and related materials controlled-depth machining using pulsed laser ablation - Cadot, Guillaume Bastien Jérémy (2017)
Pulsed laser ablation is a non-conventional machining technique that is used to machine complex parts in ultra-hard materials and for minute part geometry, which are otherwise not readily accessible with conventional tooling. The constant development of new materials with enhanced properties, as well as the demand for products with improved functionality have led to a renewed interest for alternative machining. Pulsed laser ablation is regarded as a promising technology with potential to machine a wide range of materials and shapes. The use of non-mechanical methods is advantageous due to the reduced tool-wear for ultra-hard materials and minute geometry. However, these advantages pose significant challenges since the removal rate of the material in term of shape and amount is controlled through a set of operating parameters. It is therefore necessary to have a comprehensive understanding of the process and the relation between such parameters and the effect of the laser on the surface. Furthermore, the process itself is hard to monitor online due to the short temporal and small spatial space it occurs within, and this makes it more complex to establish a detailed understanding of the process, and the optimum parameters to control the machining.